Semi-public speaking: How virtual high school debate competition increased accessibility for marginalized students - Annie Goodson (The Advocate, 2023)
The advent of online learning in the wake of the COVID-19 pandemic radically altered the landscape of modern education. While most research has examined the socio-emotional and academic impact of the shift to online school, far less attention has been given to its effect on extra-curricular activities. This article examines the ways in which virtual learning effected competitive high school debate, and how a transition to an entirely virtual debate format radically altered students’ and coaches’ experiences within the activity. Drawing on empirical studies and real-world experiences, this article underscores how virtual debate made the activity more accessible for historically marginalized communities, ultimately diversifying the activity.
Keywords: Online learning; debate; speech; rhetoric; extra-curricular activities